(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
The article examines the linguistic personality of users of Russian-language social networks through the lens of lexical and pragmatic analysis of comments. The aim of the study is to identify the key lexical, pragmatic, and communicative markers that shape linguistic personality within the framework of digital discourse. The research material consists of user comments from social networks (Telegram, VK, Instagram), collected using the method of continuous sampling. The study employs discourse analysis, pragmalinguistic analysis, and contextual analysis. The results demonstrate that linguistic personality in comments is characterized by a high degree of expressiveness, reduced normativity, active use of colloquial and evaluative vocabulary, as well as pragmatic strategies of self-presentation and influence. The practical significance of the study lies in the possibility of applying its findings in media linguistics, sociolinguistics, and applied research on Internet communication.